Transforming traditional learning in orthopaedics using mobile technology for delivery of education and training - Goh, Kian Liang; Abdul Rahman, Ahmad Zulhairi; Abdul Razak, Ardilla Hanim; Sharifudin, Mohd Ariff; Awang, Mohd Shukrimi; Noor Rahin, Mohd. Shahidan (2016)
The role of mobile applications in medical education is gaining momentum due to the rise of digital natives. Hence, there is a need to bridge the use of mobile technology and traditional education to support the undergraduate orthopaedic training in our institution particularly in the perspective of Islamic medical practice. The use of mobile technology will foreseeably increase the students’ performance in term of practical skills, interpersonal communication and self-directed learning.